A Very Rare Complication of Acute Appendicitis: Appendicovesical Fistula - Alis, Deniz (Case Rep Urol, 2016)
Appendicovesical fistula (AVF) is an uncommon type of enterovesical fistula and a very rare complication of acute appendicitis. Herein, we report a case of 39-year-old male patient who presented with persistent urinary tract infection, recurrent abdominal pain, and pneumaturia. Imaging techniques including ultrasonography (USG), computed tomography (CT), and magnetic resonance imaging (MRI) were performed to identify the abnormality. However, definitive diagnosis of AVF was made by cystoscopy.